DESIGN COMPANY IN SALES COMPUTERIZED MDS KAIN BATIK USING MICROSOFT VISUAL BASIC 6.0 - Ariyanto Ariyanto; Yudi Irawan Chandra, SKom, MMSI Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This writing explains the computerized system at the company's sales "Cain BatikMDS" which during the process is still done manually, so much the possibility oferror and is considered less effective and inefficient. Therefore, the authors provide abetter alternative to create a computerized sales system with a simple batik usingVisual Basic 6.0 programming language, which will be proposed by the authors toassist with the inputting of data processing goods through the production and salesprocess, which will then be automatically stored in a database and will exit thedisplay output to be received by the customer or purchaser as the invoice or receiptand to come to the view sales reports required by employers proficiency level in thesebatik cloth.